2014
DOI: 10.1016/j.saa.2014.01.069
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of PCBs with human serum albumin: In vitro spectroscopic study

Abstract: Following absorption, polychlorinated biphenyls (PCBs) bind to albumin and are transported via blood into the target tissues. PCBs then accumulate in tissues and induce a variety of harmful chronic and developmental effects. The aim of the present study is to determine binding parameters, such as binding constant, quenching constant, and number of binding sites for three PCB congeners (PCB118, PCB126 and PCB153) in complex with human serum albumin (HSA). The binding parameters for the complexes of HSA-PCB118, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…47 Ligand-bound crystal structures for the 66.5kDa protein show the various drug-, fatty acid-, ion-, and heme-binding sites of HSA, 48 and many methods have been employed to determine binding parameters. 41, 4951 In our present studies, we have measured the displacement of site-selective fluorescent probes from the two major drug-binding sites on HSA (i.e., Site I and Site II) as described by Sudlow et al 40 In this examination of LC-PCBs and their hydroxylated and sulfated metabolites, the displacement of: 5-dimethylamino-1-naphthalenesulfonamide (DNSA) for Site I and dansyl L-proline (DP) for Site II, shown in Figure 1, was used. 40 The displacement of these probes from their respective binding sites has been used to determine site-selectivity for ligands as well as to provide relative estimates of their binding affinities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Ligand-bound crystal structures for the 66.5kDa protein show the various drug-, fatty acid-, ion-, and heme-binding sites of HSA, 48 and many methods have been employed to determine binding parameters. 41, 4951 In our present studies, we have measured the displacement of site-selective fluorescent probes from the two major drug-binding sites on HSA (i.e., Site I and Site II) as described by Sudlow et al 40 In this examination of LC-PCBs and their hydroxylated and sulfated metabolites, the displacement of: 5-dimethylamino-1-naphthalenesulfonamide (DNSA) for Site I and dansyl L-proline (DP) for Site II, shown in Figure 1, was used. 40 The displacement of these probes from their respective binding sites has been used to determine site-selectivity for ligands as well as to provide relative estimates of their binding affinities.…”
Section: Resultsmentioning
confidence: 99%
“…49, 50 Interestingly, a separate study of PCB 118, 126, and 153 found that these compounds bound with high affinity to Sudlow Site I, with no binding to Site II. 51 These seemingly contradictory conclusions may stem from the differences in the design of the studies. 51 Although the approach reported here does not assess total protein binding, the high affinity binding of hydroxylated and sulfated LC-PCBs to HSA measured in this study underscores the importance that binding to human serum albumin may play in their subsequent distribution and effective half-lives in the body.…”
Section: Resultsmentioning
confidence: 99%
“…The results of these few studies, however, are sometimes contradictory. [163][164][165] Neurotoxic effects of PCB exposure…”
Section: Human Serum Albumin (Hsa)mentioning
confidence: 99%
“…163,165 One study, however, determined that binding occurred at Site I. 164 These seemingly contradictory conclusions stem from the differences in the studies. The latter study was based on a non-selective probe and the analysis of the intrinsic fluorescence of HSA, which can be misleading relates to the importance that albumin plays in the transplacental transfer of drugs and other compounds to the developing fetus.…”
Section: Recovery Of Pcb Sulfates Following Incubation With Hsamentioning
confidence: 99%
See 1 more Smart Citation